Aconitine: A potential novel treatment for systemic lupus erythematosus - Xiaodong Li; Liwei Gu; Lan Yang; Dong Zhang; Jianying Shen (Elsevier, 2017)
Background: Aconitum plants have been widely used in China for thousands of years. Recent evidences indicate that aconitine, the main active ingredient of Aconitum, has immunomodulatory properties that might be useful for treating autoimmune diseases, such as rheumatoid arthritis. In this study, we conducted a pilot study to explore the effect and mechanisms of aconitine on the treatment of systemic lupus erythematosus. Methods: A pristane-induced murine model was used. The pristane-induced mice were treated with aconitine (25, 75 μg kg−1 d−1, po) for 9 weeks. Every three weeks, proteinuria was detected to monitor the kidney damage and blood was collected to measure serum levels of autoantibodies, besides the kidney pathological examination. The major B cell activating factor and major pro-inflammatory mediators, PGE2, IL-17a and IL-6, were also detected. Results: We found that aconitine significantly improved the mouse health, decreased the elevated blood leukocyte counts, reduced the serum level of anti-double-stranded DNA (anti-dsDNA) antibody, greatly ameliorated renal histopathologic damage and reduced IgG deposit in glomerular. Furtherly, the levels of PGE2, IL-17a and IL-6, were found to have decreased in aconitine treated mice. Conclusion: We have demonstrated that aconitine can inhibit the progression of disease and ameliorate the pathologic lesion of systemic lupus erythematosus.